A U-shaped and alternately driven ultrasonic motor using three bending coupled modes. (1st March 2023) - Xu, Dongmei; Yang, Wenzhong; Zhang, Xuhui; Yu, Simiao; Liang, Tenglin
Abstract: Most of ultrasonic motors (USMs) using non-isomorphic hybrid modes have resonance deviation which are easy to produce frequency decoupling, and conventional USMs can only drive rotor once in a working cycle. To overcome these problems, a surface-bonded type of U-shaped USM is proposed in this paper. At the same frequency, three isomorphic fourth-order bending vibration modes can be excited simultaneously and the resonance deviation between modes is eliminated, thus reducing the effect of frequency decoupling. In addition, a fourth-order bending vibration mode on horizontal beam of the U-shaped structure is used to provide pressing force at driving feet, and bending vibration modes on two vertical beams generate driving forces. Under the excitation of orthogonal signals, alternately driven elliptical trajectories are generated at driving feet. Besides, the surface-bonded type USM is more convenient to realize miniaturization and flexible structure. The USM is analyzed by using finite element method. The prototype is fabricated to evaluate performance of the USM. The experimental results show that velocity of the USM is 89.03 mm s −1 when excitation voltage is 180 VP-P and frequency is 86 kHz. The feasibility of working principle is proved by the experimental results.